Application of SfM Method in the Earthwork Bill of Measurements (Proceedings of Faculty of Civil Engineering, 2021)
With the development of digital technologies, the possibility of their use in traditional branches such as construction has emerged. At the same time, the traditional, geodetic methods that we use in the earthwork bill of measurements can be strengthened by new digital methods such as SfM (“Structure from Motion”). The purpose of using these digital technologies is to obtain more accurate results faster. The procedure of measuring the volume with the use of SfM method from the 3D terrain model obtained from a construction site in the wider area of the city of Rijeka is presented. Models of real excavation were made with the Meshroom, Autodesk Recap, Meshlab and Blender softwares. The aim of this paper is to compare the accuracy of the results derived from the SfM method with traditional, geodetic measurement methods. The obtained result was compared to the planned excavation volume and the actual quantities from the geodetic surveys presented in the construction book. Also, the problems that arose during data collection and modeling were analyzed and the applicability of these methods in everyday practice was assessed.
Keywords: bill of measurements; photogrammetry; SfM; digitization; excavation volume